2013
DOI: 10.1111/tbed.12066
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Phylogeographic Analyses of Porcine Circovirus Type 2 Among Pig Farms in Vietnam

Abstract: This study demonstrated the prevalence of Porcine circovirus type 2 (PCV2) among pig farms in Vietnam. Analyses of the genome, capsid protein and phylogeny classified all 30 Vietnamese PCV2 strains as the PCV2b genotype, belonging to the clusters of 1A, 1B, 1C and recombinant forms. Each viral genome was 1767 nucleotides long and shared 96.0-100% nucleotide sequence identity. The amino acid substitutions in the capsid protein of the Vietnamese PCV2 strains were in immunodominant regions, and the majority of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…The antigenic index is an assessment of antigenic variation in PCV2 strains (Huynh et al., ). To further analyse the influence of mutation at important Cap sites on the antigenic feature among different PCV2 genotypes, the Jameson–Wolf antigenic index was used as a measure of antigenic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenic index is an assessment of antigenic variation in PCV2 strains (Huynh et al., ). To further analyse the influence of mutation at important Cap sites on the antigenic feature among different PCV2 genotypes, the Jameson–Wolf antigenic index was used as a measure of antigenic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Kim et al, we found that coinfection of PCV2 and M. hyo was common. In Vietnam, a study was conducted to evaluate the molecular characterization of PCV2, showing multi circulating clusters of 1A, 1B, 1C and a recombinant cluster [5]. Our study found a high seroprevalence for M. hyo infection and the likelihood that this pathogen is a cause of respiratory disease in pigs in Vietnam, which has been underestimated and for which awareness is likely to be low.…”
Section: Discussionmentioning
confidence: 79%
“…A few epidemiological and serological surveys have been conducted for major production diseases in pigs in Vietnam [2][3][4][5]. Recently, using national animal health data, the first national PRRS study was conducted to identify seasonal patterns and clusters [6].…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, it is acknowledged that Porcine circovirus type 1 (PCV1) is non-pathogenic while Porcine circovirus type 2 (PCV2) is the etiology of a devastating disease of swine, the porcine circoviral disease (PCVD) [2]. To date, PCVD is emerged in almost all swine producing countries [3], including Vietnam [4]. In 2015, in North Carolina (USA), a novel species of the genus circovirus which named Porcine circovirus 3 (PCV3) was detected for the first time from pigs suffered from porcine dermatitis and nephropathy syndrome and reproductive failure [5].…”
Section: Introductionmentioning
confidence: 99%